Temperature-dependent conformational change of two de novo proteins : Expression, purification and characterisation of two de novo proteins predicted to undergo conformational change at elevated temperatures - Lundberg,Emma (2024)
Conformational changes are essential for the function of many proteins and is determined by the sequence of amino acids and interactions between them. With computational protein design, new de novo proteins with the ability to undergo conformational changes have been designed. Also, proteins that are one amino acid apart and predicted to have two different conformational states, with the ability to change to the other one can be designed. The aims of this work was to express, purify and characterise two de novo computer-generated proteins, that are one mutation apart and could undergo conformational changes between two structures upon heating. Another aim was to mutate sequences for proteins on a trajectory. To succeed with the aims, Golden Gate Assembly was used to introduce the gene of the proteins in a plasmid. Next the protein was expressed and then analysed with mass spectroscopy, Circular Dichroism (CD) spectroscopy, Nuclear Magnetic Resonance (NMR) and crystallography. Mutations were also done. The results showed that the proteins can undergo conformational change upon heating and that the changes are partially reversible. The results also showed that mutations to the plasmid are possible. The conclusions could be drawn that the two proteins have differences in secondary structure, and that conformational changes happen in response to increased temperature. No conclusions about conformation of mutated proteins were drawn.
Keywords: biochemistry; computational protein design; conformational change; protein characterisation; protein evolution; protein expression; protein purification